2019
DOI: 10.1021/acs.jpcc.9b03722
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Spatially Inhomogeneous Electron Temperature in a Resonantly Excited Array of Bow-Tie Nanoantennas

Abstract: We studied the excitation of large-area Au bow-tie nanoantenna arrays, which we have fabricated on indium-tin-oxide (ITO)-coated glass substrates using colloidal lithography with nanoscale polystyrene colloidal particles. Ultrashort (100 fs, 800 nm) laser pulses of a Ti-Sapphire laser resonantly excite electron emission from a few tens of nanometer wide-gap regions of the array. We investigated the near-field enhanced photoemission using time-of-flight momentum microscopy. The variation of the electron emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…8,69 Conversely, we note as a parting comment that photoemission angular distributions may be utilized to elucidate nanoplasmonic field distributions for different optical parameters and particle geometries, providing complementary information to photoemission spatial distributions from photoemission electron microscopy (PEEM) studies. 9,68,69 While PEEM spatial maps with tens-of-nanometer resolution provide a clear indication of hot spots and emissive regions correlated with nanoscale structure, single-nanoparticle angleresolved photoemission studies 5,8,49,70 can provide further details on the (3D) field distributions, so long as the photoexcitation/emission dynamics can be accurately modeled. Thus, with insights from the present studies, these and other nPPE techniques may be utilized to complement electron energy loss spectroscopy, 71 super-resolution imaging, 72 and scanning near-field optical techniques 7374,75 for mapping nanophotonic fields.…”
Section: Resultsmentioning
confidence: 99%
“…8,69 Conversely, we note as a parting comment that photoemission angular distributions may be utilized to elucidate nanoplasmonic field distributions for different optical parameters and particle geometries, providing complementary information to photoemission spatial distributions from photoemission electron microscopy (PEEM) studies. 9,68,69 While PEEM spatial maps with tens-of-nanometer resolution provide a clear indication of hot spots and emissive regions correlated with nanoscale structure, single-nanoparticle angleresolved photoemission studies 5,8,49,70 can provide further details on the (3D) field distributions, so long as the photoexcitation/emission dynamics can be accurately modeled. Thus, with insights from the present studies, these and other nPPE techniques may be utilized to complement electron energy loss spectroscopy, 71 super-resolution imaging, 72 and scanning near-field optical techniques 7374,75 for mapping nanophotonic fields.…”
Section: Resultsmentioning
confidence: 99%
“…The confinement could be used to enhance processes such as for single molecule Raman spectroscopy ,, and photochemistry . A unique characterization of bowtie antennas has been demonstrated by PEEM imaging with electron energy and momentum analysis . Lehr et al have shown that the total photoemission signal from the region around the bowtie antenna tips is a result of two distinct emission mechanisms: (i) the mPP process from a transient hot electron gas, characterized by its symmetric emission in the in-plane momentum space, and (ii) a field emission process resulting from the optical near-field enhancement at the antenna tips, with strongly anisotropic emission pattern that depends on the excitation phase.…”
Section: Plasmonic Antennas and Circuitsmentioning
confidence: 99%
“…402 A unique characterization of bowtie antennas has been demonstrated by PEEM imaging with electron energy and momentum analysis. 403 Lehr et al 403 have shown that the total photoemission signal from the region around the bowtie antenna tips is a result of two distinct emission mechanisms: (i) the mPP process from a transient hot electron gas, characterized by its symmetric emission in the in-plane momentum space, and (ii) a field emission process resulting from the optical near-field enhancement at the antenna tips, with strongly anisotropic emission pattern that depends on the excitation phase. Moreover, the results in ref 403 suggest a spatially inhomogeneous distribution of the hot electron gas temperature with the thermal energy extremum localized around the gap area of the bowtie antennas.…”
Section: Plasmonic Antennasmentioning
confidence: 99%
“…Examining recent photoemission experiments with dominant surface-plasmon fields, ,, it remains difficult to disentangle the fundamental plasmon decay from the multitude of physical effects that contribute to the observed nonlinear signals, including the influence of the driving laser. A temporal separation of the material response induced by the exciting laser pulse or the plasmon could in principle be achieved for experimental conditions for which the pulse duration is much shorter than the lifetime of an LSP at a nanostructure. , But, even in those cases, experimental access to the fundamental difference between plasmonic and photonic electron excitation is denied by the inability to obtain respective photoemission signals with exactly comparable conditions, e .…”
Section: Introductionmentioning
confidence: 99%